(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
The present research is intended to investigate the autonomous learners reliance on the web-based sources of material. Nowadays English class is not the only place to learn English. It is only one place amongst multitude of opportunities for using the target language. what the students learn from the teacher and what the students learn from the web-based learning of materials will be discussed in this study.A qualitative descriptive research were conducted to answer the research questions and obtain a better understanding of the complexities of the issues under investigation. This methodology best facilitates the construction of detailed, in-depth understanding of the learning jouney of the autonomous learners. How they construct the knowledge they got from the teacher (in-class learning) and web-based sources of material (out-of-class learning).The study reveals that students learn four points from the teacher which are (1) recognizing the concrete rules of the language, (2) acknowledging the level of difficulties in language learning, (3) practicing the knowledge and (4) building the social skills. They learn two points from the web-based sources of material that are (1) acknowledging the potential of web-based sources of material and (2) having the effective judgment and learning about the western culture due to the authenticity of the language. The teacher and the web-based sources of material should be a partner and complement each other. The teacher integrates the web-based sources of materials in the learning process to effectively teach the language. However, it is not the web-based sources of material which can make any activities a fruitful and thoughtful language learning experience for the students but it is the teachers themselves. It really depends on how the teacher selects the materials, designs the tasks and activities, integrates the media with other aspects of curriculum and guides the students during the learning process.